Patient perspectives of antiretroviral pharmacy services: A cross-sectional cohort study. - Yadi Liu; Elizabeth Lyden; Renae Furl; Joshua P Havens (PLoS ONE, 2023)
Background Adherence to antiretroviral therapy (ART) remains the main predictor of sustained HIV virologic suppression for people with HIV (PWH). Mail-order pharmacy services are often offered to patients as an alternative option to traditional pharmacy services. Some payers mandate ART to be dispensed from specific mail-order pharmacies regardless of patient choice complicating ART adherence for patients affected by social disparities. Yet, little is known about patient perspectives regarding mail-order mandates. Methods Eligible patients of the HIV program at University of Nebraska Medical Center with experience receiving ART from both a local and mail-order pharmacy were invited to complete a 20-question survey with three core sections: experiences/perspectives on local and mail-order pharmacy settings; pharmacy attributes rankings; and pharmacy preference. Paired t-tests and Mann-Whitney tests were used to compare the agreement scores of pharmacy attributes. Results Sixty patients (N = 146; 41.1%) responded to the survey. Mean age was 52 years. Most were male (93%) and White (83%). The majority of participants were on ART for HIV treatment (90%) and 60% were using mail-order pharmacies for their prescription services. Significant scoring differences (p<0.05) were observed for all pharmacy attributes favoring local pharmacies. Refilling ease was the most important attribute noted. More respondents (68%) preferred local pharmacies versus mail-order pharmacies. Payer associated mail-order pharmacy mandates were experienced by 78% with half believing the mandates impacted their medical care negatively. Conclusions In this cohort study, respondents preferred local pharmacies compared to mail-order pharmacy for ART prescription services and noted ease of refilling as the most important pharmacy attribute. Two-thirds of respondents believed mail-order pharmacy mandates negatively affected their health. Insurance payers should consider the removal of mail-order pharmacy mandates to allow patient choice of pharmacy, which may help remove barriers to ART adherence and improve long-term health outcomes.